New species of the tribe Trechini from China (Coleoptera: Carabidae) - Belousov, Igor A.; Kabak, Ilya I.; Liang, Hongbin (Zootaxa, 2019)
Two new species of the tribe Trechini Bonelli, 1810 are described from the Hengduan Mountains in Sichuan and Yunnan provinces, China: Agonotrechus spinangulus sp. n. (from the Kangwu Pass, Liziping Town, Muli County, southern Sichuan) and Sinotrechiama yunnanus sp. n. (from the Xiaobaicaoling Pass, Santai Town, Dayao County, Yunnan). A new collecting site (Yizi Pass between Meigu County and Ebian County, Sichuan) is provided with some data on morphological variation for one more species, Protrechiama crassipes (Uéno, 1997), known so far only from the two female specimens of the type series. These new findings significantly expand our knowledge of the above three genera. Sinotrechiama yunnanus sp. n. is the first member of the genus found outside of Sichuan Province.